Testing the acoustic tolerance of harbour porpoise hearing for impulsive sounds - Klaus Lucke; Paul Lepper; Marie-Anne Blanchet; Ursula Siebert (2008)
The planned construction of offshore wind turbines in the North and Baltic Seas involves the emission of high numbers of intense impulsive sounds when turbine foundations are driven into the ground by pile driving. Based on knowledge about other odontocete cetaceans (Finneran et al. 2002), it can be assumed that the source levels, which will on average exceed 225 dB re 1 μPa at 1 m, bear a risk at least for temporary threshold shift (TTS) in the auditory system of harbour porpoises Phocoena phocoena that inhabit these waters. In order to base the definition of noise-exposure criteria on information on the acoustic tolerance of this species to single impulses, an auditory study was conducted.